Prevalence and incidence of neuropsychiatric disorders in post hospitalized COVID-19 patients in South America: a systematic review and meta-analysis - Perea-Flórez, Francisco; Javier-Murillo, Nair; Lapeyre-Rivera, André; Gamonal, Bryan; Cabanillas-Lazo, Miguel; Velásquez-Rimachi, Victor; Alva-Diaz, Carlos (Frontiers in Psychiatry, 2023)
Introduction There are multiple reports of neuropsychiatric disorders (NDs) such as stress, depression, post-traumatic stress disorder (PTSD), or anxiety, in patients who have survived the acute phase of COVID-19, being even more frequent in people who were hospitalized with moderate or severe disease. South America (SA) was one of the most affected continents during this time due to its health, social, political and economic context. We aimed to determine the prevalence and incidence of NDs in patients following hospitalization for COVID-19 in SA. Materials and methods We searched in PubMed, Embase, Scopus, Web of Science, LILACS, SciELO, and Google Scholar databases up to October 2022. We performed proportion meta-analysis with a random-effect model and Freeman-Tukey Double Arcsine transformation using the STATA 16.1 program. Finally, we evaluated heterogeneity by subgroup analysis and certainty of evidence with the GRADE approach. Results We included eight studies from four countries. We only pooled six studies with prevalence measures. The estimated prevalence of all NDs was 31.48% (two-studies, 95%CI: 25.82–37.43). Depression, anxiety, insomnia, PTSD, and memory alterations had a pooled prevalence of 16.23% (three-studies, 95%CI: 7.18–27.93, I2: 94.22), 18.72% (three-studies, 95%CI: 11.65–26.97, I2: 87.56), 43.07% (three-studies, 95%CI: 32.77–53.37, I2: 92.61), 31.78% (three-studies, 95%CI: 14.33–52.40, I2: 97.96), and 38.24% (two-studies, 95%CI: 35.5–40.97), respectively. The evidence included was deemed as moderate to high certainty. Conclusion We suggest that NDs should be prioritized in research and care in South America with public policies that can support their identification and prompt management to improve the quality of life of patients. More studies are needed to adequately study the prevalence of NDs in South America, their associated factors, and evaluate the causes of heterogeneity. Systematic review registration https://doi.org/10.6084/m9.figshare.21901041.v1.